"Like you failed at life": Debt, health and neoliberal subjectivity. (September 2018) - Sweet, Elizabeth
Abstract: The need to more explicitly incorporate political economy and neoliberalism into research on social inequalities in health has been acknowledged across disciplines. This paper explores neoliberalism as it relates to consumer financial debt and internalized feelings of personal responsibility and failure for adults in Boston, Massachusetts. Using data from a mixed-methods study (n = 286), findings show that endorsing a neoliberalized view of personal debt as failure is associated with significantly worse health across a range of measures, including blood pressure, adiposity, self-reported physical and emotional symptoms, depression, anxiety, and perceived stress, even when controlling for several socio-demographic confounders. Results are discussed within the context of both neoliberal economic policies that funnel consumers into chronic debt and neoliberal sociocultural ideologies that promote self-judgments of indebtedness as personal failure. Findings highlight the importance of neoliberalism as an important contemporary social determinant of health and suggest new directions for research to explore. Highlights: For some, financial indebtedness results in a sense of personal 'failure'. Those who feel like a 'failure' have worse physical and emotional health. This feeling is embedded in neoliberal policy and ideology. As such, it can be seen as a type of neoliberal subjectivity (NS). NS may be an important social determinant of health more generally.